Determination Of Selected Organochlorine Pesticides In Farmers’ Biological Samples Using Gas Chromatography-Mass Spectrometry And Their Knowledge, Attitude And Practice Towards Pesticides Use - Noor, Juliana Mohd (2011)
This study was conducted in agricultural areas in Pinang Tunggal, Kepala Batas, Penang. The main objective of the study was to determine the level of selected organochlorine pesticides in farmers’ biological samples particularly in hair and urine samples by using Gas Chromatography – Mass Spectrometry (GC-MS). Concomitantly, it was also carried out to assess the farmers` knowledge, attitude and practice towards pesticide use. Organochlorine pesticides selected in this study were HCHs (α-, β-, γ- and δ-hch), DDTs (p,p’-ddt, p,p’-ddd and p,p’-dde), aldrin, dieldrin, endosulfan sulfate, heptachlor, heptachlor epoxide and methoxychlor.